2012
DOI: 10.1080/00071668.2012.659654
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary nucleotide supplementation on performance and development of the gastrointestinal tract of broilers

Abstract: 1. Two experiments were conducted to determine the effects of dietary nucleotide supplementation on broiler performance, and physical and morphological development of the gastrointestinal tract. 2. Experiment 1: A total of 180 one-d-old male chicks were placed in battery brooders in 3 × 6 replicate pens containing 10 chicks each. Chicks were randomly assigned to one of the three dietary treatments; a maize-soyabean meal based diet supplemented with 0, 0·25, and 0·50% Torula yeast RNA (as a source of nucleoti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 12 publications
2
28
0
4
Order By: Relevance
“…Among the various drawbacks in the use of antibiotic growth promoters as feed additives are the imbalance of normal microflora, and reduction in beneficial intestinal microflora that might affect intestinal turn-over and maturation of gut immuno-cells (Sen et al, 2012). Yeast-derived macromolecules can have immunomodulatory, cell growth promoting, and pathogen microbe controlling capacity in chickens, turkeys, and pigs (Solis de los Santos, 2007;Jung and Batal, 2012). Nucleotides in YDM have been shown to play a role in improving performance of birds (Bradley et al, 1994;Van Buren and Rudolph, 1997).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the various drawbacks in the use of antibiotic growth promoters as feed additives are the imbalance of normal microflora, and reduction in beneficial intestinal microflora that might affect intestinal turn-over and maturation of gut immuno-cells (Sen et al, 2012). Yeast-derived macromolecules can have immunomodulatory, cell growth promoting, and pathogen microbe controlling capacity in chickens, turkeys, and pigs (Solis de los Santos, 2007;Jung and Batal, 2012). Nucleotides in YDM have been shown to play a role in improving performance of birds (Bradley et al, 1994;Van Buren and Rudolph, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, yeastderived macromolecules (YDM) have been studied as immunomodulators and nutritional supplements in promoting cell growth and controlling pathogenic microbes in chickens, turkeys, and pigs (Solis de los Santos, 2007;Fasina and Thanissery, 2011;Superchi et al, 2012). A typical YDM composition includes a blend of yeast-derived nucleotides, inositol, protein, glutamic acid, vitamins, and minerals, among others (Jung and Batal, 2012). It has been suggested that the beneficial action of yeast macromolecules as supplements is brought about by the nucleotide content of the product (Savage and Zakrzewska, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…These conditions are commensurate to gastrointestinal damage occasioned by Eimeria infection (9). Evaluations of nucleotide rich yeast extracts on growth, feed efficiency and intestinal development and health has been reported in broiler chickens (86,87,135,136). However, there are limited studies assessing the effects of dietary nucleotide supplementation on development of immune organs in broilers challenged with Eimeria.…”
Section: Utility Of Nucleotide Rich Yeast Extracts In Modulating Coccmentioning
confidence: 99%
“…Efeitos positivos da inclusão dos nucleotídeos à dieta de leitões recém-desmamados, frangos e peixes têm sido verificados no ganho de peso (ABREU et al, 2010;BONTEMPO et al, 2006), no consumo de ração (SAUER et al, 2012), na conversão alimentar (GHOSH et al, 2012;JUNG;BATAL, 2012;TAHMASEBI-KOHYANI et al, 2011), na morfologia…”
Section: Diarreia Pós-desmameunclassified
“…intestinal (BONTEMPO et al, 2006;JUNG;BATAL, 2012;SAUER et al, 2012), na microbiota intestinal (ANDRÉS-ELIAS et al, 2007;GHOSH et al, 2012) e no sistema imune dos animais (ANDRÉS-ELIAS et al, 2007;TAHMASEBI-KOHYANI et al, 2011). 190 54,190 54,190 54,190 54,190 Farelo de soja (46%) 18,000 18,000 18,000 18,000 18,000 Soro de leite (71% de lactose) 2 11,400 11,400 11,400 11,400 11,400 Leite em pó (37% de lactose) 5,160 5,160 5,160 5,160 5,160 Plasma desidratado 5,000 5,000 5,000 5,000 5,000 L-Lisina.HCl (78%) 0,280 0,280 0,280 0,280 0,280 DL-Metionina (99%) 0,120 0,120 0,120 0,120 0,120 L-Treonina (98,5%) 0,080 0,080 0,080 0,080 0,080 Produto comercial: Clorohidroxiquinolina (60,0 %).…”
Section: Diarreia Pós-desmameunclassified